2005
DOI: 10.1021/jp052930g
|View full text |Cite
|
Sign up to set email alerts
|

Acetone Oxidation Using Ozone on Manganese Oxide Catalysts

Abstract: Supported manganese oxide catalysts were prepared by the impregnation of alumina foam blocks washcoated with alumina and silica. The manganese content based on the weight of the washcoats was 10 wt % calculated as MnO2. Fourier transform profiles of the Mn K-edge EXAFS spectra for these samples gave three distinctive peaks at 0.15, 0.25, and 0.32 nm and were close to the profiles of Mn3O4 and beta-MnO2. The number of surface active sites was determined through oxygen chemisorption measurements at a reduction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…For the XRD patterns of RuO 2 -MnO 2 /CNTs, as shown in Figure 3, only a few broad peaks with less intensity at around 2h = 18.1/ and 37.0/, attributed to MnO 2 (200) and MnO 2 (400) [29,31] [32][33][34]. As to the RuO 2 / CNTs, the main peak is at 75°C, which attributes to the reduction of most RuO 2 to Ru.…”
Section: Characterisation Of Ruo 2 -Mno 2 /Cntsmentioning
confidence: 99%
“…For the XRD patterns of RuO 2 -MnO 2 /CNTs, as shown in Figure 3, only a few broad peaks with less intensity at around 2h = 18.1/ and 37.0/, attributed to MnO 2 (200) and MnO 2 (400) [29,31] [32][33][34]. As to the RuO 2 / CNTs, the main peak is at 75°C, which attributes to the reduction of most RuO 2 to Ru.…”
Section: Characterisation Of Ruo 2 -Mno 2 /Cntsmentioning
confidence: 99%
“…It has been reported that ozone decomposed to O 2 on supported manganese oxide catalysts as expressed by Eqs. (1-3), where * denotes active sites on the catalyst [11,21,22].…”
Section: Structure Of Alumina-supported Manganesementioning
confidence: 99%
“…Although numerous studies were conducted on the catalytic ozonation of VOCs [16][17][18][19][20][21][22][23], the underlying mechanism and its relevant kinetic steps remain unclear [24]. Other than the recent study by Rezaei and Soltan [24], no studies were performed to test the validity of the L-H s mechanism on the catalytic ozonation of toluene over alumina-supported manganese oxide catalysts.…”
Section: Introductionmentioning
confidence: 99%